2014
DOI: 10.1371/journal.pone.0107366
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Scleractinian Coral Recruits Using Fluorescent Censusing and DNA Barcoding Techniques

Abstract: The identification of coral recruits has been problematic due to a lack of definitive morphological characters being available for higher taxonomic resolution. In this study, we tested whether fluorescent detection of coral recruits used in combinations of different DNA-barcoding markers (cytochrome oxidase I gene [COI], open reading frame [ORF], and nuclear Pax-C intron [PaxC]) could be useful for increasing the resolution of coral spat identification in ecological studies. One hundred and fifty settlement pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 64 publications
(81 reference statements)
4
12
1
Order By: Relevance
“…Of the 101 colonies sampled, 85 (84%) clustered with P. verrucosa (clade 2, Fig. 2 ), and match published mtORF references of this species ( Schmidt-Roach et al, 2012 ; Pinzón et al, 2013 ; Hsu et al, 2014 ; Marti-Puig et al, 2014 ; Gélin et al, 2017b ). A total of 15 (15%) clustered with the complex of species P. meandrina and P. eydouxi (clade 3, Fig.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Of the 101 colonies sampled, 85 (84%) clustered with P. verrucosa (clade 2, Fig. 2 ), and match published mtORF references of this species ( Schmidt-Roach et al, 2012 ; Pinzón et al, 2013 ; Hsu et al, 2014 ; Marti-Puig et al, 2014 ; Gélin et al, 2017b ). A total of 15 (15%) clustered with the complex of species P. meandrina and P. eydouxi (clade 3, Fig.…”
Section: Discussionsupporting
confidence: 73%
“…They represent the dominant P. verrucosa haplotypes found in this study as they count for 93% of the genotyped P. verrucosa colonies. They were also previously found in coral recruits in the shallow waters of Kenting, southern Taiwan ( Hsu et al, 2014 ). In our study haplotype H8 was not found at 15 m. However, we suspect that this haplotype could be present at this depth given that it was collected at all other depths.…”
Section: Discussionsupporting
confidence: 56%
“…To this end, combinations of different genes, including mitochondrial and nuclear loci, have been proposed and used for different groups of anthozoans (Huang et al 2011) and the 28S rDNA for flatworms (Litvaitis and Rohde 1999, Litvaitis and Newman 2001). In anthozoans, species-level resolution is still limited due to frequent hybridisation (Quattrini et al 2019), resulting in low interspecific divergence (Shearer and Coffroth 2008, Dohna and Kochzius 2015), though these markers are possibly useful at the genus level (Hsu et al 2014). Other mitochondrial markers such as cytochrome b (Ward et al 2005, Sevilla et al 2007), 12S rRNA (Miya et al 2015) and D-loop control region (Lee et al 1995) have been suggested for use on barcoding fish species.…”
Section: Discussionmentioning
confidence: 99%
“…eydouxi ; according to the descriptions of previous South African checklists [17,18]. The three SSHs were then correlated to current accepted morpho-genetic species designations from contemporary literature [5,7,8,10,11,26,27,29,30,66] and a collated study including all ORF haplotypes [4]; SSH09a related to P . eydouxi/meandrina , SSH13a related to P .…”
Section: Resultsmentioning
confidence: 99%